Introduction of The Magical of Science to arise Elementary School Students' Interest in Science in the Indonesia-Malaysia Border Area - Riski Muliyani; Yudi Kurniawan (STKIP Singkawang, 2022)
This program was carried out in the Indonesia-Malaysia border area, precisely in Jagoi Babang District, Gersik Village. The purpose of holding this service is to attract the interest of elementary school students, especially in border areas in learning science. The method used in this program was in the form of scientific demonstrations using household materials (daily utensils and food ingredients) by official team to 22 elementary students at State Elementary School 04 PAUM, Paum Hamlet, Gersik Village, Jagoi Babang District, Bengkayang Regency. The projects that were demonstrated included: 1) Anti-shatter magic balloons, 2) Anti-nail magic balloons, 3) Magic Plastics, 4) Automatic balloon blowers, 5) The bending rays and, 6) Magic Glass. The results of the program shown that the students’ interest of science at State Elementary School 04 PAUM were quite positive where 90% (20 students) gave positive statements about the activity, students 5% (1 student) did not give a response, and 5% (1 student) gave a negative response to the activity of this program sequences. These results provide an early description that science lessons for elementary school age children are quite requested if they are delivered using interesting methods